The WORK–FAMILY CONFLICT, WORKLOAD, AND WORK–LIFE BALANCE: A MODERATED MODEL OF COWORKER SUPPORT - Siregar, Tika (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
The concept of work-life balance has emerged as a significant concern in recent years. Maintaining a positive work-life balance is crucial for overall well-being and productivity. This study aims to analyze the effect of work-family conflict and workload on work-life balance and to examine the moderating role of coworker support. The sample for this investigation comprised 250 employees from the strartup companies located in West Sumatra. Data acquisition was achieved through the distribution of online questionnaires. The analysis of the data was performed utilizing Structural Equation Modeling (SEM). The findings demonstrate that work-family conflict and workload exert a substantial impact on the work-life balance of employees. In addition, it was revealed that coworker support alleviates the adverse effects of work-family conflict and workload on work-life balance.